Concepções em disputa sobre educação profissional no contexto da redemocratização brasileira - Sá, Mara Franco de (2016)
This dissertation is linked to the line of research entitled Education, Labor and Social Movements)”, of the Education Post-Graduate Program, from the Faculty of Education of the Federal University of Goiás. It analyzes the conceptions of Professional Education in dispute in the context the re-democratization of the country, trying to understand how they were built and consolidated by the collective subjects that supported them. The research is qualitative and methodologically made use of documental and bibliographical research. At documental research were prioritized as sources: the Proceedings of the Brazilian Education Conference; Minutes of the 9th, 12th, 13th, 16th and 23th meetings of the 8th Sub-Committee on Education of the National Constituent Assembly of 1987; the educational proposals of the Brazilian Society for the Science Progress (SBPC), the Catholic Education Association (AEC) and the Interstate Federation of Educational Institutions Workers (FITEE), used for the elaboration of the education chapter in the Federal Constitution of 1988, as well seven (07) meeting records of the Federal Chamber and the Law Projects 1258/88 and 101/93, about the directives and bases of education. The bibliographical research concerned the Capitalist State in the twentieth century from reading Harvey (1993) and Chenais (1996). We also adopted Anderson (1995) and Bóron (1995) to the reflections about the neoliberalism in advanced economy countries and in Latin America. About the concepts of work, in contemporaneous capitalism, and the precariat was based on Standing (2014). For the study of political party reorganization and the National Constituent Assembly, in 1987, we used the discussions of Schmitt (2015), Mainwaring (2001), Barbosa (2010) and Madeira (2006). The dissertation analyzes the conceptions of professional education in three distinct moments: (i) in the Brazilian Education Conferences (CBEs); (ii) during the National Constituent Assembly, from 1987; and (iii) in the legislative debate from which resulted the Law No. 9394/96. The reflections derived from the research reveal that the conceptions in dispute about the professional education point to the game of political forces in the context of re-democratization; at this conjuncture, the academic and scientific institutions stand out in their role of resistance in regard to the fight in defense of the public school for all, and in the movement against the maintenance of conservative proposals in education, with the support of the urban and rural popular movement and the trade union movement and political party as well.